Corporate Reputation on Mass Media, Public Opinion, and YouTube: Examining the Factors Influencing Reputation of Fortune 500 Companies. Issue 4 (November 2016) - Meadows, Cui; Meadows, Charles
Abstract This study investigated the relationships of the mass media, public opinion, and social media strategies regarding corporate reputation. We collected data from content analyses of television news reports and official corporate YouTube videos, and then compared the data with a public opinion survey about corporate reputation. By doing so, this study hopes to confirm the influence of mass media and recognize the role of social media in shaping and influencing corporate reputation. Results indicated that YouTube salience promotes corporate reputation. The correlation between a corporation's mass media agenda and YouTube agenda supports the concept of intermedia agenda setting, meaning one media's agenda setting influences another media's agenda. Further, we found that the salience of substantive attributes in media coverage and in YouTube channels is significantly related with the corporations' reputation scores. This study extends the factors influencing corporate reputation and recognized the role of social media strategies. These findings are promising in helping examine the complex relationship among the mass media, social media, and corporate reputation.